(untitled) (Scientific journal of the Fergana State University, 2024)
On the purpose of steady developing of the countryside, working up recommendations according to main courses of geoecologic-economic perfection. Systematic analysis and synthesis, comparative geography, historic-geographic, economic-statistical, cartography, countryside extension, score evaluation and so on. Bases of scientific-research methods on geoecologic-economic condition for Ferghana region as a rural area has been elaborated. Factors that made an effect on rural localities for the last 100 еars have been studied, on the basis of current geoecologic-economic evaluation scale, and reformation of ethnoecologic culture of rural areas, preservation of ecologic-economic balance in countryside, reduction of agrodemographic pressure, and the course of developing traditional and innovative branches of rural economy has been defined. In this research work, the geo-ecological and economic state of rural areas is studied using the example of the Fergana region and the following conclusions and scientific and practical recommendations for its improvement are developed. In our republic, the theoretical basis of geographical research in rural areas has been enriched with a new direction. Until now, the main attention in the geographical study of rural areas has been focused on the geographical study of the economy and population, that is, such topics as “village economy” and “village population” have been studied. The “location, territory, ecology of the village”, which is important for geographical research, was left behind by researchers. Therefore, this study pays attention to the “places”, “territory” of the village, and the geo-ecological aspects of its use on the farm. As is observed in other objects of geography research, when studying rural areas, the importance of ecological-geographical research increases. In this direction, in geographical studies of rural areas, great importance was attached to the scale, magnitude, duration and territorial aspect of the impact of the economy and population on nature. Based on the level of resistance of rural areas to external anthropogenic influences and an assessment of the current situation, traditional and modern methods have been developed to improve the geo-ecological and economic condition. Using the example of the Fergana region, which has a special ethno-ecological culture, natural-agrarian potential, demographic situation and economic potential, a landscape planning program has been developed aimed at improving the use of rural areas, and for this, factors that indirectly influence the formation of the existing geo-ecological and economic situation of rural areas are taken into account. territories have been identified and studied.